The viral storm : the dawn of a new pandemic age - Wolfe, Nathan (New York : Times Books, 2011)
The author, a Stanford biologist reveals the surprising origins of the world's most deadly viruses, and how we can overcome catastrophic pandemics. He discussses the complex interactions between humans and viruses, and the threat from viruses that jump from species to species. He tells the story of how viruses and human beings have evolved side by side through history; how deadly viruses like HIV, swine flu, and bird flu almost wiped us out in the past; and why modern life has made our species vulnerable to the threat of a global pandemic. His research missions to the jungles of Africa and the rain forests of Borneo have earned him the nickname "the Indiana Jones of virus hunters," and in this book he takes readers along on his groundbreaking and often dangerous research trips to reveal the surprising origins of the most deadly diseases and to explain the role that viruses have played in human evolution. In a world where each new outbreak seems worse than the one before, he points the way forward, as new technologies are brought to bear in the most remote areas of the world to neutralize these viruses and even harness their power for the good of humanity. His provocative vision of the future will change the way we think about viruses, and perhaps remove a potential threat to humanity's survival. -- Provided by publisher.
"The "Indiana Jones" of virus hunters reveals the complex interactions between humans and viruses, and the threat from viruses that jump from species to species"--Provided by publisher.
Introduction -- Gathering clouds. The viral planet ; The hunting ape ; The great microbe bottleneck ; Churn, churn, churn -- The tempest. The first pandemic ; One world ; The intimate species ; Viral rush -- The forecast. Virus hunters ; Microbe forecasting ; The gentle virus ; The last plague.
Includes bibliographical references and index.
Keywords: Viruses; Virus diseases; Molecular evolution; Human evolution; SCIENCE / Life Sciences / General; Virus Diseases; Pandemics; Viruses